Research Methods for Studying Narrative Identity: A Primer. (July 2017) - Adler, Jonathan M.; Dunlop, William L.; Fivush, Robyn; Lilgendahl, Jennifer P.; Lodi-Smith, Jennifer; McAdams, Dan P.; McLean, Kate C.; Pasupathi, Monisha; Syed, Moin
This article provides a primer for researchers seeking an introduction to quantitative narrative research methods. It represents a consensus document of most common practices used by the coauthors. Key elements of conducting narrative research (e.g., asking narrative questions, designing narrative prompts, collecting narratives, coding narratives) are discussed along with limitations to this approach and future directions.